2004
DOI: 10.1152/ajplung.00256.2003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic interaction between airway epithelial cells andStaphylococcus aureus

Abstract: Staphylococcus aureus is a major cause of pulmonary infection, particularly in cystic fibrosis (CF) patients. However, few aspects of the interplay between S. aureus and host airway epithelial cells have been investigated thus far. We investigated by videomicroscopy the time- and bacterial concentration-dependent (104, 106, and 108CFU/ml) effect of S. aureus on adherence, internalization, and the associated damage of the airway epithelial cells. The balance between the secretion by S. aureus of the α-toxin vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 37 publications
4
39
0
Order By: Relevance
“…However, Weinrauch et al (52) showed that low doses of ␣-toxin induce DNA fragmentation and cell death, whereas high doses result in massive necrosis without DNA fragmentation. In agreement with Da Silva et al (10), who have worked on the same MM-39 cell line, we observed a prominent necrosis phenotype of the MM-39-cells, with a transient apoptotic process 9 h after interaction (Fig. 5).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, Weinrauch et al (52) showed that low doses of ␣-toxin induce DNA fragmentation and cell death, whereas high doses result in massive necrosis without DNA fragmentation. In agreement with Da Silva et al (10), who have worked on the same MM-39 cell line, we observed a prominent necrosis phenotype of the MM-39-cells, with a transient apoptotic process 9 h after interaction (Fig. 5).…”
Section: Discussionsupporting
confidence: 93%
“…Fluorescent images were recorded every 30 min for 24 h as previously described (10). Variations of the YO-PRO-1 and of the propidium iodide fluorescence intensities were expressed as the ratio of the fluorescence intensity at a given time to the initial fluorescence intensity.…”
Section: Evaluation Of Airway Epithelial Cell Death By Apoptosis or Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulation of apoptosis is a very complex phenomenon, and the analysis of the MEC transcriptome in the various conditions of stimulation tested in our study confirms this complexity. Moreilhon et al (34) also reported the presence of antiapoptotic genes in airway cells stimulated by Sp, and to a lesser extent by Sa, whereas many other reports show proapoptotic mechanisms consecutive to an infection (5,30,48,52). As a result we cannot make a clear conclusion about apoptosis; a large increase in MEC apoptosis might reveal degradation of the mammary gland tissue and so an alteration of its functioning, whereas enhanced apoptosis might be also a normal phenomenon with the cell turnover.…”
Section: Mec Responses To Live S Aureus or Bacterial Supernatantmentioning
confidence: 97%
“…S. aureus surface proteins such as adhesins and protein A are produced during exponential growth phase, whereas most exoproteins, including toxins, hemolysins, and tissue-degrading enzymes, are secreted during the stationary phase. Alpha-toxin, one of the major soluble VF of S. aureus, is able to induce transient apoptosis followed by the necrosis of human airway epithelial cells (HAEC) (9). We have also recently shown that live S. aureus and more predominantly soluble VF in contact with HAEC induce marked alterations in the transcriptional expression profile of HAEC associated with activation of the NF-B and activator protein (AP)-1 pathway, upregulation of PGE 2 and cyclooxygenase (COX)-2 expression and proinflammatory cytokine release such as IL-1␤ and IL-8 (23).…”
mentioning
confidence: 99%